Deficient skeletal muscle regeneration after injury induced by a Clostridium perfringens strain associated with gas gangrene - Zúñiga Pereira, Ana Mariel (2019)
Gas gangrene, or clostridial myonecrosis, is usually caused by Clostridium perfringens and may occur spontaneously in association with diabetes mellitus, peripheral vascular disease, or some malignancies but more often after contamination of a deep surgical or traumatic lesion. If not controlled, clostridial myonecrosis results in multiorgan failure, shock, and death, but very little is known about the muscle regeneration process that follows myonecrosis when the infection is controlled. In this study, we characterized the muscle regeneration process after myonecrosis caused in a murine experimental infection with a sublethal inoculum of C. perfringens vegetative cells. The results show that myonecrosis occurs concomitantly with significant vascular injury, which limits the migration of inflammatory cells. A significant increase in cytokines that promote inflammation explains the presence of an inflammatory infiltrate; however, impaired interferon gamma (IFN-γ) expression, a reduced number of M1 macrophages, deficient phagocytic activity, and a prolongation of the permanence of inflammatory cells lead to deficient muscle regeneration. The expression of transforming growth factor β1 (TGF-β1) agrees with the consequent accumulation of collagen in the muscle, i.e., fibrosis observed 30 days after infection. These results provide new information on the pathogenesis of gas gangrene caused by C. perfringens, shed light on the basis of the deficient muscle regenerative activity, and may open new perspectives for the development of novel therapies for patients suffering from this disease.